Pendampingan Pembuatan Produk SANTRI (Sabun Cair Antibakteri) Berbasis Ekstrak Daun Sirih pada Kelompok PKK - Rinawati, Rinawati; Akmal, Jamiatul; Juliasih, Ni Luh Gede Ratna; Ning Tyas, Marsanda Nur Wahyu; Kiswandono, Agung Abadi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2024)
The mentoring activity for making dishwashing soap with betel leaf extract in Gebang Village aims to increase the independence and welfare of the local community, especially for Micro, Small, and Medium Enterprises (MSMEs). This program is implemented as an effort to optimize local natural potential, especially betel leaf plants which are known to have antibacterial and natural cleaning properties. This activity involves several stages, starting from education about the benefits of betel leaves, technical training in making soap, to mentoring in aspects of product packaging and marketing.The method used includes a participatory approach, where the community is invited to be actively involved in every process, so that a sustainable transfer of knowledge and skills is created. The results of this activity show that the community is able to produce effective, environmentally friendly dishwashing soap that is competitive in the local market. In addition, participants are also given training on simple business management, including bookkeeping, determining selling prices, and marketing strategies.This mentoring has a positive impact on increasing the capacity of individuals and the village economy, especially in creating local superior products with high selling value. It is hoped that with these new skills, the community can improve their standard of living and make making dishwashing soap one of the sustainable businesses in the village.